Peer to Peer The Commons Manifesto - Bauwens , Michel (Critical Digital and Social Media Studies, 2019)
"Not since Marx identified the manufacturing plants of Manchester as the blueprint for the new capitalist society has there been a more profound transformation of the fundamentals of our social life. As capitalism faces a series of structural crises, a new social, political and economic dynamic is emerging: peer to peer. What is peer to peer? Why is it essential for building a commons-centric future? How could this happen? These are the questions this book tries to answer. Peer to peer is a type of social relations in human networks, as well as a technological infrastructure that makes the generalization and scaling up of such relations possible. Thus, peer to peer enables a new mode of production and creates the potential for a transition to a commons-oriented economy. "